Urban violence: history and Ethiopians dilettante to learn from it, 1916–1991 - Yalemzewd Dessie (Cogent Social Sciences, 2024)
AbstractIn Ethiopia, urbanization and urban violence are recent phenomena dating back to the beginning of the twentieth century. In the country’s long history, politics and urban violence have been bedfellows and reliable means of change, devolution, and reform. Since 1916, Ethiopia has essentially experienced more violence in its urban’s than in its rural areas due to recurrent episodes of political instability at the national level. Ironically, Ethiopian leaders were amateurs who were unable to draw lessons from their past deeds. Nevertheless, Ethiopian historiography has devoted little attention to the magnitude of political issues-related urban violence in Ethiopia. As a result, the paper attempted to analyse two goals. First, it tries to analyse the historical events of Ethiopian urban violence from 1916–1991, and secondly, it tries to explain the tradition of Ethiopian leaders to learn from past deeds. To document this extraordinary theme, the paper grey on both primary sources and published secondary literature that have been available to the writer to date. The collected data was systematically verified, analyzed, and interpreted through qualitative data analysis.